LITERATUR REVIEW: PENGARUH KENYAMANAN DIDALAM LINGKUNGAN KERJA TERHADAP KUALITAS KERJA - Septiani Septiani; Suci Fitriani (PT Naureen Digital Education, 2023)
The long-term success of the company depends on the importance of people because many of the resources of the company itself can be imitated, except for its human resources. So, it is necessary to carry out activities such as training and debriefing for employees. Training is an important indicator provided to employees and is an investment made by people. In the case of employees, participation in training programs, which are paid for by the company, can enable them to feel special and increase their knowledge and skills. Even though there is intense competition for the various jobs available, many organizations experience fairly high employee turnover rates. The employee turnover rate varies from country to country. However, the main cause is job dissatisfaction. Organizational processes also determine the extent to which employees are satisfied with their jobs. The intrinsic and extrinsic motivation of employees, as well as organizational context (policies, procedures, systems, and culture and climate), affect employee satisfaction with the existing organizational system. In this article, 2 main points will be discussed, the first is to investigate the relationship between training activities and human motivation as a function of resource management to understand the role of training activities in increasing employee motivation and the second is to examine the determinants of employee comfort and their effect on job satisfaction. , as well as separation and performance; defines employee satisfaction as employee happiness/pleasure at work triggered by employee intrinsic and extrinsic motivation and organizational context, and considers employee satisfaction as an important factor affecting personnel job satisfaction.